Unveiling the Biomarkers: Identifying Key Signatures for Cancer Hallmarks - Verma, Shikha; Sharan, Aditi (EAI Endorsed Transactions on Pervasive Health and Technology, 2024)
INTRODUCTION: Finding biomarkers that are closely associated with cancer-related traits is critical to the advancement of cancer research, especially when it comes to personalised treatment. The objective of this research is to explore multiple biomarker categories, including genetics, proteins, and chemicals, in order to better understand the complex terrain of cancer. OBJECTIVES: Few of the objectives include examining a variety of biomarker types, such as chemical, protein, and genetic markers and determining which important biomarker signatures correspond to each cancer hallmark. Also the study aims to perform a comparative analysis to show how the SVM model’s features incorporating identified biomarkers improves classification performance. METHODS: The study includes NLP and ML techniques for the identification and classification of biomarkers for the hallmark of cancer dataset. RESULTS: The discovery of important biomarker signatures connected to every cancer hallmark is one of the study’s primary findings. In addition, our new SVM-based classification model performed well in the multilabel text classification of PubMed abstracts, showing a significant improvement in performance when the biomarkers were used as features. CONCLUSION: To sum up, this study makes a substantial contribution to the area of cancer research by identifying important biomarker signatures connected to many cancer hallmarks.